THE HISTORY OF THE AMIR TEMUR ERA IN WESTERN HISTORIOGRAPHY (American Journal of Research in Humanities and Social Sciences, 2026)
This article scientifically analyzes the study of Amir Temur and the Timurid period in Western historiography, as well as the views of European scholars, writers, and orientalists. It examines how the image of Sahibqiran was portrayed in Western literature and historical sources, and how his state administration, military strategy, and cultural heritage were evaluated.